Peningkatan Kompetensi Kelompok KKG-MI melalui Pengembangan E-Modul dengan Formative Assessment Tools - Fauziah, Zumrotul; Anisah, Giati; Wulandari, Pramesti; Cahyani, Ambar Dwi; Amiludin, Muchamat; Nisa, Siti Nur Mukaromatun; Sa’adah, Lailatus (Universitas Nusantara PGRI Kediri, 2025)
This study aims to improve the skills of elementary school (MI) teachers in developing e-modules using formative assessment tools for reading and writing learning. The mentoring activity was carried out in Malo District, Bojonegoro Regency, involving the Elementary School Teacher Working Group (KKG-MI). This mentoring focused on training in making interactive e-modules using the Canva application and integrating formative evaluation tools such as quizzes and practice questions. In addition, teachers were also trained to convert e-modules into flipbook format using the Heyzine application, in order to increase the interactivity and attractiveness of learning. The results of this activity indicate that MI teachers in Malo District have new abilities in designing e-modules that are effective and interesting for students, and the application of formative assessment tools in e-modules allows teachers to evaluate student understanding more measurably. The results of this study have been able to realize the targets and objectives in community service, namely a) improving the competence of MI teachers in using e-modules, b) encouraging the implementation of a structured reading-to-write learning model, and c) introducing and optimizing the use of formative assessment tools. Based on these results, this community service is able to increase student motivation in learning to read and write as well as improving technological skills for teachers. This activity is expected to be continued and expanded to other areas to support improving the quality of technology-based education in Madrasah Ibtidaiyah.